2015
DOI: 10.1371/journal.pone.0133831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Convective Heat and Mass Transfer in Flow of Powell-Eyring Fluid Past an Exponentially Stretching Sheet

Abstract: The aim here is to investigate the effects of convective heat and mass transfer in the flow of Eyring-Powell fluid past an inclined exponential stretching surface. Mathematical formulation and analysis have been performed in the presence of Soret, Dufour and thermal radiation effects. The governing partial differential equations corresponding to the momentum, energy and concentration are reduced to a set of non-linear ordinary differential equations. Resulting nonlinear system is computed for the series soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Similar ranges are studied in the models for stretching sheet induced flow of [50,40,39,21]. In Figure 2 we show the temperature and volume fraction for the case Sc = 5, Nb = 0.1, Nt = 0.5, Pr = 10 and again we take ∆T =10 K. The solid line in the figures is the solution of (16-18), dash-dot that of equations (22,23). From Figure 2a) we observe that the temperature predicted by the previous models is significantly higher than that of the current model.…”
Section: Model Comparisonmentioning
confidence: 84%
See 1 more Smart Citation
“…Similar ranges are studied in the models for stretching sheet induced flow of [50,40,39,21]. In Figure 2 we show the temperature and volume fraction for the case Sc = 5, Nb = 0.1, Nt = 0.5, Pr = 10 and again we take ∆T =10 K. The solid line in the figures is the solution of (16-18), dash-dot that of equations (22,23). From Figure 2a) we observe that the temperature predicted by the previous models is significantly higher than that of the current model.…”
Section: Model Comparisonmentioning
confidence: 84%
“…These extensions and modifications include magnetohydrodynamic effects; radiative heat flux in the heat equation; permeable substrates; heat generation/absorption; non-Newtonian fluids; flow in a cylindrical geometry; flow in a cylindrical geometry embedded in a porous medium; a permeable cone in a porous media; various far-field flow configurations; nanofluids with micro-organisms, see [8,22,25,52,55,56,59,65]. Simply for the stretching sheet model there are studies with sheets moving at a constant rate, with velocity proportional to distance x; proportional to x n ; proportional to x/t (and then with a substrate temperature proportional to x/t 2 ); exponentially increasing [8,12,23,54,57].…”
Section: Introductionmentioning
confidence: 99%
“…Mustafaa et al [16] reported the impact of convective boundary condition on the heat transfer characteristics past an exponentially stretching sheet in a nanofluid considering the thermophoresis and Brownian motion effects. Hayat et al [17] studied the effects of convective heat and mass transfer in the flow of Eyring-Powell fluid past an inclined exponential stretching surface. Rahman et al [18] investigated the steady boundary layer flow and heat transfer characteristics of a nanofluid past an exponentially shrinking surface with convective boundary condition.…”
Section: Introductionmentioning
confidence: 99%
“…These processes obtain high temperature, which the flow is subjected to the convective boundary condition. Therefore, a number of studies on boundary layer flows with a convective boundary condition, including mixed convection boundary layer flow [20][21][22][23][24][25][26][27] and a stretching sheet [28][29][30][31][32][33][34][35], have been reviewed since then. Motivated by the above researchers, the purpose of this research paper is to develop the system of MHD mixed convection heat transfer of an electrically conducting fluid over an exponentially stretching continuous surface with an exponential temperature distribution.…”
Section: Introductionmentioning
confidence: 99%